IC-ENC ENC Validation Training Course - Tyzack, Laura; Gkionis, Panagiotis (The International Hydrographic Review, 2014)
The International Centre for ENCs (IC-ENC) was set up in 2002 with a remit to harmonise the production and distribution of high quality ENCs. This Note provides an insight into IC-ENC, its validation processes, and the new ENC Validation Training Course. It is jointly authored by Lt.Cdr. Panagiotis Gkionis (Hellenic Navy Hydrographic Service, ENC Validation Training Course delegate) and Miss Laura Tyzack (IC-ENC Data Validator).